Prescribers' views and experiences of using direct acting oral anticoagulants in the management of nonvalvular atrial fibrillation: A survey in remote and rural Scotland. Issue 10 (2nd August 2019) - Generalova, Daria; Cunningham, Scott; Leslie, Stephen J.; Rushworth, Gordon; McIver, Laura; Stewart, Derek
Abstract : Aims: A recent systematic review highlighted the lack of robust studies on prescribers' perspectives of direct‐acting oral anticoagulants (DOACs) for nonvalvular atrial fibrillation. The aim was to determine prescribers' views and experiences of prescribing DOACs. Methods: A cross‐sectional survey of prescribers in a remote and rural area of Scotland. Survey items were: demographics; prescribing of DOACs; views of potential influences on DOAC prescribing; knowledge of prescribing guidelines; and experiences. Items on potential influences were based on the Theoretical Domains Framework. Data were analysed using descriptive and inferential statistics, and content analysis of responses to open questions. Principal component analysis was performed on the items of potential influences. Results: In total, 154 responses were received, 120 (77.9%) from doctors, 18 (11.7%) from nurse prescribers and 10 (6.4%) from pharmacist prescribers (6 missing). Principal component analysis of the Theoretical Domains Framework items of potential influences gave 4 components. Component scores for (i) role of professionals, their knowledge and skills and (ii) influences on prescribing were positive. Those for (iii) consequences of prescribing and (iv) monitoring for safety and effectiveness were more neutral. There were low levels of agreement for statements relating to DOACs being more effective, safer and cost‐effective than warfarin. There were similar responses around the complexity of bleeding management and detection of over and under‐anticoagulation. Conclusion: This study has identified several key issues of DOAC prescribing (e.g. bleeding management) hence further emphasis is required in continuing professional development and during guideline implementation and evaluation.